Contemporary Interpretation of Asnaf Muallaf and Its Management Model: Evidence from Majlis Islam Sarawak - Fadzil Hazim Samah; Nik Abdul Rahim Nik Abdul Ghani (Bulletin of Islamic Research, 2025)
The management and distribution of zakat to the asnaf muallaf (new converts to Islam) represent a critical aspect of social finance. Although discussions regarding muallaf have been ongoing for centuries, there exist diverse interpretations of the asnaf muallaf category among the four major Islamic schools of thought. Various interpretations have been proposed concerning the definition of muallaf and the necessity of continuing zakat distribution to this group. This study aims to explore the concept and management model of muallaf within the Islamic Council of Sarawak (Majlis Islam Sarawak or MIS). Employing a qualitative approach, the study utilizes document analysis and interviews to gather information. The findings reveal that zakat distribution in Sarawak is predominantly focused on muallaf who have recently embraced Islam. However, individuals inclined toward Islam, who are also included in the MIS's interpretation, appear to receive less explicit attention in the implementation of zakat distribution. This study is expected to contribute to the enhancement of asnaf muallaf management in Sarawak and serve as a reference for zakat institutions and religious bodies in improving zakat administration for the asnaf muallaf group.